P60 Clinical characteristics, complications, and anticoagulation in children with infective endocarditis: a single center experience from turkey. (June 2019) - Kosger, Pelin; Keskin, Tugcem; Kiztanir, Hikmet; Kirel, Birgul; Ucar, Birsen
Abstract : Objective: In this study, the data of our patients diagnosed with infective endocarditis (IE) between 2010–2018 at the Eskişehir Osmangazi University Faculty of Medicine Hospital, Department of Pediatric Cardiology were retrospectively obtained. Methods: Demographic data, the presence of a predisposing cardiac disease, presentation with complaints, clinical and laboratory findings, blood culture results, treatment plans, evolving complications, and the echocardiographic data of eleven patients were examined. The relevant features of the patients with complications, of those having anticoagulant therapy in addition to antibiotherapy, those who underwent surgery, and those who showed a mortality course were determined. Results: The youngest patient was 7 months old and the oldest was 14 years old (7.5 ± 4.6 years). All of the cases had congenital heart anomalies: four had cyanotic congenital heart disease (CHD), four had a ventricular septal defect (VSD), two had a bicuspid aortic valve (BAV), and one patient had a secundum atrial septal defect (ASD). There were no cases with rheumatic heart disease. Three patients with cyanotic CHD were treated with corrective cardiac surgery. A total of eight patients had embolic findings; five at the time of admission and three at follow-up. Nine patients received antibiotics prior to admission. Echocardiography showed vegetation in nine patients. Anticoagulant treatment was applied to 2 patients with mitral valve and aortic valve vegetation in addition to antibiotic treatment. The most common microorganism in the blood culture was coagulase negative staphylococcus with 5 cases and 2 of them were identified as staph. epidermidis. The second most common microorganism was the viridans group streptococcus with 4 cases. Four patients underwent early surgical treatment, one patient died due to multiple organ failure caused by systemic embolization, and one patient died due to sudden hemodynamic instability in the first week of follow-up. Conclusion: IE is a serious disease with life-threatening complications, where the number of at-risk patients due to CHD is gradually increasing and thus the mortality rate has not decreased despite improved medical and surgical treatment procedures. Early initiation of appropriate antibiotic treatment following early diagnosis is has great importance in preventing mortality.Considering the complications that may be caused by early surgical intervention, anticoagulant therapy, which is combined with antibiotherapy in appropriate patients, can be tried as a useful option prior to committing to early surgery.